1971
DOI: 10.1111/j.1365-2621.1971.tb02058.x
|View full text |Cite
|
Sign up to set email alerts
|

DIETARY EFFECTS ON BEEF COMPOSITION. 4. Processing and Palatability Attributes

Abstract: The influence of dietary regimen of 104 half-sib Angus steers allotted to 1 of 13 combinations of hay, corn silage and corn concentrate, and of slaughter weights of 284 vs. 340 kg and 409 vs. 454 kg (live weight) on processing qualities and palatability of beef was studied. Measurements included postmortem glycolytic activity, water-and fat-binding capacity, textural properties, cooking losses, flavor and juiciness of selected muscles. Results showed that feeding regimens had a greater effect than did slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Variation in beef palatability due to nutritional treatment has been reported by Jacobson andFenton (1956), Garrigus et al (1969), Dube et al (1971), Kropfet al (1975), Bowling et al (1977), Smith et al (1979 and Burson et al (1980). These authors noted a decrease in beef palatability due to a lower plane of nutrition.…”
Section: Introductionmentioning
confidence: 66%
“…Variation in beef palatability due to nutritional treatment has been reported by Jacobson andFenton (1956), Garrigus et al (1969), Dube et al (1971), Kropfet al (1975), Bowling et al (1977), Smith et al (1979 and Burson et al (1980). These authors noted a decrease in beef palatability due to a lower plane of nutrition.…”
Section: Introductionmentioning
confidence: 66%
“…May et al (1989) in-10.0 1 9.0 dicated that carcasses from grass-fed steers had higher pH than carcasses from steers finished on concentrate for a minimum of 84 days. The higher pH in carcasses from grass-fed cattle was attributed to two factors: (1) grass-fed steers are thought to be more susceptible to pre-slaughter stress (Bowling et al, 1977), (2) grass-fed steers tend to have less glycogen in their muscle which results in a smaller decrease in pH during rigor (Dube et al, 1971). Data by other researchers, however, suggested that, as demonstrated in our study, diet did not influence pH.…”
Section: Resultsmentioning
confidence: 96%
“…Conversely, no significant difference in flavors existed between the grass and grain diets-fed animals [73]. The less desirable flavors were also seen on meats from the hay diets-fed animals compared to corn silage diets [74], while Oltjen et al (1971) [75] showed the opposite results. It has been hypothesized that majority of flavor effects due to feeding of forages is mainly due to changes in fatty acid compositions.…”
Section: The Factors Affect Aroma Flavors 31 Effect Of Dietsmentioning
confidence: 91%